Specification of Curve Selection and Supported Curve Parameters in MSR ECCLib - Bos, Joppe; Costello, Craig; Longa, Patrick; Naehrig, Michael (Microsoft Research, 2015)
This document explains the details of the curve generation algorithms and provides the parameters for the NUMS (Nothing Up My Sleeve) curves. These curves are supported in the MSR Elliptic Curve Cryptography Library (MSR ECCLib).